2021
DOI: 10.1007/s00415-021-10782-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis epidemiological trends in Italy highlight the environmental risk factors

Abstract: Italy is definitely a high-risk country for multiple sclerosis (MS). Over the last 50 years, several epidemiological studies, including longitudinal surveys, have disclosed that MS incidence and prevalence in Italy mainland and Islands (Sardinia and Sicily) have progressively increased, picturing a semi-parabolic curve. Based on the comprehensive scrutiny of 58 papers, we conclude that the latitude risk gradient does not fit to the Italian map of MS. The genetic heterogeneity of the Italian ethnicities, that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The authors suggested that this might be due to lower vitamin D levels in mountain dwellers caused by limited access to sunlight in mountain environments, exposure to magnetic fields and other factors related to the highaltitude environment, as well as a higher incidence of infections that may play a role in the development of MS (23, 24). However, in a study conducted in Italy by Puthenparampil et al (25), no such connection was found. According to the authors, genetic or other environmental factors in the Italian highlands do not have the same impact on the incidence of MS as in Switzerland (25).…”
Section: Negative Impact Of Mountainous Terrain On Ms Patientsmentioning
confidence: 88%
“…The authors suggested that this might be due to lower vitamin D levels in mountain dwellers caused by limited access to sunlight in mountain environments, exposure to magnetic fields and other factors related to the highaltitude environment, as well as a higher incidence of infections that may play a role in the development of MS (23, 24). However, in a study conducted in Italy by Puthenparampil et al (25), no such connection was found. According to the authors, genetic or other environmental factors in the Italian highlands do not have the same impact on the incidence of MS as in Switzerland (25).…”
Section: Negative Impact Of Mountainous Terrain On Ms Patientsmentioning
confidence: 88%
“…A latitudinal prevalence gradient also exists in Latin America between Panama and Argentina [ 6 ]. However, the latitude gradient did not fit an Italian map for MS, especially in the islands of Sardinia and Sicily [ 7 ]. Living in a high UV-B environment with summer exposure during childhood in the years leading up to MS onset was associated with a lower MS risk [ 8 ].…”
Section: Background and Introductionmentioning
confidence: 99%
“…MS is characterized by five major phenotypes, namely the clinically isolated syndrome (CIS), relapsing-remitting (RR), primary progressive (PP), progressive-relapsing (PR), and secondary progressive MS (SP) [4,5]. The same risk factors, i.e., genetic patterns, tobacco smoking, exposure to air pollutants, viral infections, low vitamin D levels, and juvenile obesity [6,7], also affect the type and severity of the disease. Other factors unrelated to demographic and clinical features, like the variability of contacts, diagnostic paths, and therapeutic capabilities, may also influence the MS phenotypes.…”
Section: Introductionmentioning
confidence: 99%